2012
DOI: 10.1007/s11920-012-0285-8
|View full text |Cite
|
Sign up to set email alerts
|

What can Cognitive Neuroscience Teach us about Anorexia Nervosa?

Abstract: Anorexia nervosa (AN) is a complex illness and highly challenging to treat. One promising approach to significantly advance our understanding of the underlying pathophysiology of AN involves developing a cognitive neuroscience model of illness. Cognitive neuroscience uses probes such as neuropsychological tasks and neuroimaging techniques to identify the neural underpinnings of behavior. With this approach, advances have been made in identifying higher order cognitive processes that likely mediate symptom expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Despite high genetic heritability estimates [Kaye et al, ], our knowledge of the biological underpinnings of this devastating illness is very limited [Kaye et al, ]. The use of modern noninvasive neuroimaging techniques may allow a deeper understanding of AN [Kidd and Steinglass, ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite high genetic heritability estimates [Kaye et al, ], our knowledge of the biological underpinnings of this devastating illness is very limited [Kaye et al, ]. The use of modern noninvasive neuroimaging techniques may allow a deeper understanding of AN [Kidd and Steinglass, ].…”
Section: Introductionmentioning
confidence: 99%
“…Functional MRI has advanced our understanding of the neural differences between people with ED and their healthy counterparts. Altered activity in the insula (Kim, Ku, Lee, Lee, & Jung, ) and abnormalities in the processing of rewards (Avena & Bocarsly, ; Bohon & Stice, ; Brooks et al, ; Dichter, Damiano, & Allen, ; Holsen et al, ; Stice, Spoor, Bohon, Veldhuizen, & Small, ) in addition to alterations in frontal regions have been reported (Brooks et al, ; Celone, Thompson‐Brenner, Ross, Pratt, & Stern, ; Hollmann et al, ; Marsh et al, ; Uher et al, ), and subsequent neural models of ED have been developed (Brooks, Rask‐Andersen, Benedict, & Schioth, ; Kidd & Steinglass, ; Marsh, Steinglass, et al, ; Steinglass & Walsh, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cognitive functioning has received increased attention as a possible factor in the development and maintenance of AN (Bühren, Holtkamp, Herpertz-Dahlmann, & Konrad, 2008;Kaye, Wierenga, Bailer, Simmons, & Bischoff-Grethe, 2013;Kidd & Steinglass, 2012;Treasure & Schmidt, 2013). Previous studies have reported weaknesses in cognitive flexibility (operationalized as set-shifting) and central coherence in AN, which might play a role in the compromise response to therapy and the poor prognosis (Danner et al, 2012;Shott et al, 2012;Tenconi et al, 2010).…”
mentioning
confidence: 99%